Availability and maintenance modelling for systems subject to multiple failure modes - Qiu, Qingan; Cui, Lirong; Gao, Hongda (Computers & industrial engineering, 2017)
•A maintenance model is formulated for a competing-risk system.•The analytical results on system availability are derived.•The optimal maintenance policy maximizing steady-state availability is obtained.•The optimal maintenance policy minimizing long-run average cost rate is derived. The availability and optimal maintenance policies of a competing-risk system undergoing periodic inspections are studied in this paper. Specifically, a repairable system with a working state and M failure modes is considered. Each failure mode has a random failure time. When the system fails from the ith(i=1,2,…,M) failure mode, corresponding corrective repair is performed which takes a random time Yi(i=1,2,…,M). Some analytical results on the instantaneous availability and the steady-state availability for the system are derived. The model is then utilized to obtain the optimal inspection interval that maximizes the system steady-state availability or minimizes the average long-run cost rate. A numerical example for Remote Power Feeding System is presented to demonstrate the application of the developed approach.